REAKTIVASI DAN PEREMAJAAN PERPUSTAKAAN SDN 07 BEKASI JAYA - Sutisna, Delvianisa; Alrasyid, M Harun (DEVOSI, 2020)
Library is a means in which reading activities occur. The library includes a room, part of a building or a separate building that contains collection of books, which are arranged and arranged in such a way, so that it is easy to find and use when needed by the reader. With the school environment library, students can add insight and knowledge outside class hours. The implementation of this activity is filing books, labeling books, tidying books on the shelves according to the collection, repainting the library room and giving a touch of wall stickers on the side of the room. After carrying out the â€œLibrary Rejuvenationâ€ activities for SDN 07 Bekasi Jaya students there was an increase in the number of free visits to the library from before the library rejuvenation was carried out. SDN 07 Bekasi Jaya students are happy with the library rejuvenation.